HPV vaccinations in males; Knowledge, attitudes, and practices of physicians on human papilloma virus vaccinations for their sons : Physicians’ attitudes on HPV vaccination for their sons - Seyfettinoglu, Sevtap; Dağoğlu Hark, Betül (Journal of Surgery and Medicine, 2023)
Background/Aim: The Human Papilloma Virus (HPV) infection is the most common sexually transmitted disease and has been shown to cause cancer. Both sexes have a lifetime risk of at least 50% of exposure to HPV. Male HPV vaccinations can yield advantages for both the individual and community, including reduced transmission of HPV and protection of male and female health. The approval of vaccinations is mainly influenced by parental perspectives on this matter. It is essential to examine the subject in terms of physicians, who have the highest knowledge about HPV in society. This cross-sectional study aims to investigate physicians' attitudes and knowledge about vaccinating their male children against the human papillomavirus. Methods: A total of 1670 physicians were included in this study. Working as a physician and having a son were determined as inclusion criteria. A digital questionnaire was given to the physicians participating in the study. The answers to the survey questions were rated on a 4-point Likert scale (agree, do not know, disagree, strongly disagree). The responses were compared with the variables, and statistical analysis was performed. Results: Of the physicians participating in the study, 34.4% were male and 65.6% were female. A small percentage of the physicians (6.2%) reported that they would vaccinate their boys against HPV, and 59.9% of them indicated that they would not but they would consider it. The physicians’ who were most likely to vaccinate their sons worked in the fields of radiology (97.3%), orthopedics (80%), and gynecology (78.8%). It was determined that the physicians who said they would never have their sons vaccinated against HPV were most frequently specialists in anesthesiology and reanimation, infectious diseases, and clinical microbiology. Conclusions: This study determined that physicians in some specialties hesitated to give the HPV vaccine to their sons. The HPV vaccine is crucial for boys, and it is essential to point out the significance of providing seminars to physicians, particularly in developing nations like Turkey, regarding this issue and its consequences.